2013
DOI: 10.1123/jab.29.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hopping Frequency on Bilateral Differences in Leg Stiffness

Abstract: Understanding the degree of leg stiffness during human movement would provide important information that may be used for injury prevention. In the current study, we investigated bilateral differences in leg stiffness during one-legged hopping. Ten male participants performed one-legged hopping in place, matching metronome beats at 1.5, 2.2, and 3.0 Hz. Based on a spring-mass model, we calculated leg stiffness, which is defined as the ratio of maximal ground reaction force to maximum center of mass displacement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…The results also agree with previous ones showing no significant difference between dominant and no-dominant legs in vertical stiffness in cyclical rebound jumping tasks (Flanagan & Harrison, 2007), in unilateral hoping tasks at 2.2 Hz (Brauner, Sterzing, Wulf, & Horstmann, 2014), and in unilateral hoping tasks at 1.5, 2.2 and 3.0 Hz (Hobara et al, 2013). In addition, in the study of Dalleau, Belli, Bourdin, and Lacour (1998) stiffness did not differ significantly between legs in a 4-min treadmill run at a velocity corresponding to 90% of VO 2max .…”
Section: Lower Limb Dominance and Stiffness Symmetrysupporting
confidence: 94%
See 1 more Smart Citation
“…The results also agree with previous ones showing no significant difference between dominant and no-dominant legs in vertical stiffness in cyclical rebound jumping tasks (Flanagan & Harrison, 2007), in unilateral hoping tasks at 2.2 Hz (Brauner, Sterzing, Wulf, & Horstmann, 2014), and in unilateral hoping tasks at 1.5, 2.2 and 3.0 Hz (Hobara et al, 2013). In addition, in the study of Dalleau, Belli, Bourdin, and Lacour (1998) stiffness did not differ significantly between legs in a 4-min treadmill run at a velocity corresponding to 90% of VO 2max .…”
Section: Lower Limb Dominance and Stiffness Symmetrysupporting
confidence: 94%
“…A better understanding of leg stiffness would be beneficial for the development of injury prevention strategies (Hobara, Inoue, & Kanosue, 2013) as, according to Flanagan and Harrison (2007), stiffness imbalances between the lower limbs could be detrimental to performance or could increase the risk of injury.…”
Section: Introductionmentioning
confidence: 99%
“…increasing the height of the box and subsequent vGRF upon landing) was not examined in the current study due to the training/skill level of the participants and should be explored in future investigations. Whilst intuitively, it may seem that increasing intensity would result in larger K vert asymmetries, this relationship has not been observed during unilateral hopping (Hobara et al, 2013).…”
Section: Discussionmentioning
confidence: 85%
“…Nonetheless, it is not unexpected that the higher vGRFs associated with drop jumping may result in less negative COM displacement. For example, it has been reported that displacement during bilateral hopping is reduced as hopping frequency, and subsequent vGRF, are increased (Hobara et al, 2013(Hobara et al, , 2014.…”
Section: Discussionmentioning
confidence: 97%
“…Prior to the experiment, limb dominance was determined by asking the participants which leg they preferred to use when kicking a ball, and the limb reported by the participant was identified as the dominant leg 21,22. After being fitted with the braces, the participants immediately moved to the experiment area.…”
Section: Methodsmentioning
confidence: 99%